Autoantibodies and Cytokines - Ali Khan, Wahid (IntechOpen, 2019)
The mechanism of autoantibodies cannot be explained without the detail knowledge of cytokines and interferon. These active molecules of immunology are very much dependent on each other and their function cannot be completed without their interaction towards each other. Currently, this the most updated book on this subject that helps the readers/students to upgrade their knowledge by going through chapter by chapter. Contribution by the renounced authors across the globe makes this book really unique and consider as one of the most updated textbook on this subject. This book provides a comprehensive guide to the function and types of autoantibodies and cytokines in basic and clinical field.